AVALIAÇÃO DO COMPORTAMENTO HIGROTÉRMICO DE UM RESFRIADOR EVAPORATIVO EM ADOBE - CAMILA CATHERINE DE MORAIS CASSUNDÉ (2024)
The use of evaporative cooling to preserve food using artisanal construction techniques on land is an alternative to provide more autonomy for vulnerable communities, but studies are needed to prove its efficiency. An adobe evaporative cooler with a capacity for 1 ton of produce was developed and built by Davalo (2021) and required additional studies of behavior and efficiency. Thus, this research aimed to determine the best operating conditions of this cooler through complementary real measurements of hygrothermal performance and determine its best operating conditions, contributing to improving the selection and analysis of the cooler's typical behavior, due to the multiple variables that interfere with its behavior in the open air, analyze the influences of climatic conditions to achieve maximum cooling efficiency with the least use of water, in addition to considering the increase in cooler performance through the use of adobes in the efficiency of evaporative cooling. This work, of an experimental nature, involves secondary (literature review) and primary (measurement) data with statistical analysis of results. Three on-site measurement cycles were carried out, with the third cycle showing the best results in volumes 0l, 100l, and 200l, with a greater temperature difference (12.1°C with 100l of irrigation), greater humidity gain (66. 4% with 200l of irrigation) and greater cooling efficiency (96.5% with 200l of irrigation). The 200l irrigation volume obtained the most promising results among the four, considering the highest cooling efficiency using the least amount of water. Keywords: food safety, thermal efficiency; thermal behavior; hygroscopicity; Earth; ZECC; post-harvest storage; evaporative cooling;